Closed Circuit Television CCTV Installation, Maintenance and Operation. - Cieszynski, Joe. (Elsevier, 2003)
Closed Circuit Television (CCTV) surveillance is one of the important areas in the security industry. This book provides information for professionals involved in the installation and maintenance of CCTV systems, system design, specification and purchasing and the management of CCTV systems.